Dendritic Mesoporous Silica Nanoparticles for pH‐Stimuli‐Responsive Drug Delivery of TNF‐Alpha. Issue 13 (29th May 2017) - Kienzle, Arne; Kurch, Sven; Schlöder, Janine; Berges, Carsten; Ose, Robert; Schupp, Jonathan; Tuettenberg, Andrea; Weiss, Henning; Schultze, Jennifer; Winzen, Svenja; Schinnerer, Meike; Koynov, Kaloian; et al.
Abstract : Tumor necrosis factor‐alpha (TNF‐α) is a pleiotropic immune stimulatory cytokine and natural endotoxin that can induce necrosis and regression in solid tumors. However, systemic administration of TNF‐α is not feasible due to its short half‐life and acute toxicity, preventing its widespread use in cancer treatment. Dendritic mesoporous silica nanoparticles (DMSN) are used coated with a pH‐responsive block copolymer gate system combining charged hyperbranched polyethylenimine and nonionic hydrophilic polyethylenglycol to encapsulate TNF‐α and deliver it into various cancer cell lines and dendritic cells. Half‐maximal effective concentration (EC50 ) for loaded TNF‐α is reduced by more than two orders of magnitude. Particle stability and premature cargo release are assessed with enzyme‐linked immunosorbent assay. TNF‐α‐loaded particles are stable for up to 5 d in medium. Tumor cells are grown in vitro as 3D fluorescent ubiquitination‐based cell cycle indicator spheroids that mimic in vivo tumor architecture and microenvironment, allowing real‐time cell cycle imaging. DMSN penetrate these spheroids, release TNF‐α from its pores, preferentially affect cells in S/G2/M phase, and induce cell death in a time‐ and dose‐dependent manner. In conclusion, DMSN encapsulation is demonstrated, which is a promising approach to enhance delivery and efficacy of antitumor drugs, while minimizing adverse side effects. Abstract : Dendritic mesoporous silica nanoparticles are used to encapsulate the highly toxic antitumor drug TNF‐α. Efficiency of the employed system is tested in 2D and 3D tumor cell cultures. Encapsulation in mesoporous silica nanoparticles is a promising approach to enhance delivery and efficacy of antitumor drugs is demonstrated, while minimizing adverse side effects.